Nanoporous Gold by Alloy Corrosion: Method-Structure-Property Relationships. Issue 4 (4th March 2017) - Graf, M.; Roschning, B.; Weissmüller, J.
Abstract : Nanoporous gold (NPG) made by selective corrosion, or dealloying, serves as a model system for the investigation of electrochemical and mechanical properties of nanomaterials. While various dealloying protocols are in use, it is typically assumed that the structural characteristics are identical and independent of the preparation technique. Yet, reported properties such as strength, Young's modulus, or catalytic behavior can vary widely. Here, we compare the microstructure and the mechanical behavior of NPG structures prepared by three different synthesis protocols reported in the literature. We find that corrosion rates, the content of residual sacrificial metal, the average ligament size and the densification by shrinkage strongly depend on the synthesis protocol and show the consequences on the mechanical properties. We finally deduce different correlations between microstructure and composition for different dealloying routes.